Description Fear of Missing Out (FoMO) in Undergraduate Students at Faculty of Nursing - Kintan Komala; Imas Rafiyah; Witdiawati Witdiawati (Universitas Padjadjaran, 2022)
Social media makes it easy for internet users to communicate that is not limited by time and place. Excessive use of social media can have a negative impact, namely Fear of Missing Out (FoMO). FoMO on students will have an impact on increasing the duration of smartphone use while studying in class which can interfere with learning concentration and reduce students' academic achievement. This study aims to determine the description of Fear of Missing Out (FoMO) in undergraduate students of the Faculty of Nursing, Padjadjaran University. This study uses a quantitative descriptive design. The population of this study was nursing students of an undergraduate program with active status in the even semester of the 2020/2021 academic year at Padjadjaran University. The sampling technique used in this study was stratified random sampling with a value of e = 5% (0.05), a sample of 242 students was obtained. The instrument used in this study was the Fear of Missing Out scale (FoMOs). Data analysis in this study is univariate analysis using the mean and standard deviation. Based on the results of this study, it was found that most of the respondents experienced moderate level of FoMO (67.8%), then a small proportion were at low level of FoMO (16.9%) and high level of FoMO (15.3%). The conclusion of this study is that most respondents experience moderate level of FoMO, education and counseling are needed for students regarding Fear of Missing Out. Future researchers can conduct more in-depth research on the factors and impact of FoMO on nursing students.